PROCOMIDA, a food-assisted maternal and child health and nutrition program, contributes to postpartum weight retention in Guatemala: A cluster-randomized controlled intervention trial - Leroy, Jef L.; Olney, Deanna K.; Ruel, Marie T. (American Society for Nutrition, 2019)
Food-assisted maternal and child health and nutrition (FA-MCHN) programs are widely used to reduce household food insecurity and maternal and child undernutrition in low- and middle-income countries. These programs, however, may unintentionally lead to excessive energy intake and unhealthy weight gain, especially in food-secure populations.